Workplace cardiovascular risk reduction by healthcare professionals—a systematic review. (20th August 2021) - Zusman, E Z; Kapanen, A I; Klaassen, A; Reardon, J
Abstract: Background: Cardiovascular disease has a significant impact on public health and is largely preventable by addressing modifiable risk factors. As most adults spend on average half of their waking hours at work, this provides a significant opportunity to address modifiable risk factors through health promotion interventions. Healthcare professionals have the knowledge and skills to provide workplace interventions aimed at cardiovascular risk reduction. Aims: This study was aimed to assess the literature regarding the effect of workplace interventions led by healthcare professionals on cardiovascular risk factors. Methods: Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, MEDLINE, PsycINFO and SPORTDiscus were systematically searched from inception to March 2021. Included studies evaluated impact of workplace interventions by healthcare professionals on cardiovascular health. Data on study design, baseline characteristics, interventions, outcomes and conclusions were extracted and qualitatively analysed. Results: Forty-five studies representing 77 633 participants were included in the analysis. Healthcare professionals involved included: nurses, nurse practitioners, physicians, dietitians, pharmacists, physician assistants, medical technicians/emergency medical technicians and physiotherapists. Workplace interventions by healthcare professionals generally improved surrogate markers of cardiovascular health. Success varied based on provider and nature of the intervention. Addressing motivation and including follow-up were key factors for successful intervention to reduce cardiovascular risk factors. Conclusions: Workplace health promotion initiatives delivered by healthcare professionals may improve cardiovascular risk markers if they are evidence based and customized for target populations. More research is needed to determine clinical relevance of interventions and ideal interventions for specific employee groups.